THE DECLINE OF THE CZECHOSLOVAK MARRIAGE AND THE ECONOMIC IMPACT OF THE VELVET DIVORCE - Angela Velkova (European Scientific Journal, ESJ, 2013)
The article investigates differences in the transformation of Czech and Slovak economies and how these affected the overall economic development of the studied countries upon the dissolution of Czechoslovakia i.e. the Velvet Divorce. A contrastive comparison is embraced to grasp disparities in the transfer of one formerly centralized command economy with state-owned firms operating under the planned economy organization into two independent market economies under sovereign governance. Notwithstanding the common language and history, the Czech Republic and Slovakia underwent distinct transition processes crucial for the economic rise of the former and the development stagnation of the latter. The legal vacuum and the absence of strong monitoring over capital transformation on one hand, and a corrupted government and autocratic leadership on the other, ushered in scandalous privatizations with major Slovak firms depreciated and appropriated by small political elite without injecting capital or any significant restructuring of the corporate organization. The perpetuated growth of unemployment rates and fall in productivity illustrated by GDP decline, started to alarm for growing anomalies in the Slovak economic system as a whole, exhibiting ubiquitous distortions and a contiguous stagnation. These negative implications drew roots particularly from the imprudent economic policies of the first years of Slovak transition (1993- 1998), until national elections had removed the first Prime-minister of independent Slovakia- Vladimir Mečiar from the Office. The Czech Republic led by Vaclav Klaus, meanwhile, benefited from a more responsible and democratic rule that put the Czech economy back on track and paved the way to its early integration within the EU market. Needless to say, the profiles of the first leaders of the independent republics of the Czechs and the Slovaks played an indispensable role in countries’ overall progress or retrogression and their international recognition respectively. The main purpose of the article, therefore, entails an interdisciplinary identification of discrepancies in transition processes in the Czech Republic and Slovakia detrimental to the perpetuated and still observable disparities between the two countries in terms of economic development and standards of living.